ROLE OF DIVIDEND POLICY IN INCREASING THE INVESTMENT ATTRACTIVENESS OF COMPANIES - Omonov Sardor Ulmasovich (European Science Publishing, 2025)
This article studies the views of various economists on dividend policy in studying the role of dividend policy in increasing the investment attractiveness of companies in the capital market. The mathematical foundations of dividend policy, internal and external factors affecting dividend policy are analyzed. Based on the analysis, relevant conclusions are formed.
Keywords: Dividend policy, dividend, dividend payouts, investment attractiveness, capital market, shareholder, investor, issue, issuer.